2021
DOI: 10.1038/s41393-020-00609-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial aspects of health-related quality of life and the association with patient-reported bladder symptoms and satisfaction after spinal cord injury

Abstract: Study Design: Prospective, multi-centered, observational Objectives: To characterize the relationship between psychosocial aspects of health-related quality of life (HRQoL) and patient-reported bladder outcomes. Setting: Multi-institutional sites in the United States, cohort drawn from North America Methods: We performed a cross-sectional analysis of data collected as part of the multicenter, prospective Neurogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…In another recent analysis using the NBRG SCI registry, individuals with SCI with higher positive affect and well-being scores were observed to have better bladder-related QoL than those with lower scores. 18 We found the same relationship in this analysis, with worse bladder symptoms and satisfaction associated with higher pain, and better symptoms and satisfaction associated with better positive affect and well-being. In one study by Etingen et al, the authors observed that longer duration from injury was associated with improved pain interference when also accounting for positive affect/well-being and life satisfaction.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In another recent analysis using the NBRG SCI registry, individuals with SCI with higher positive affect and well-being scores were observed to have better bladder-related QoL than those with lower scores. 18 We found the same relationship in this analysis, with worse bladder symptoms and satisfaction associated with higher pain, and better symptoms and satisfaction associated with better positive affect and well-being. In one study by Etingen et al, the authors observed that longer duration from injury was associated with improved pain interference when also accounting for positive affect/well-being and life satisfaction.…”
Section: Discussionsupporting
confidence: 78%
“…Psychosocial measurement of HRQoL, which are several panels from the SCI-QoL measurement system, utilize computer-adaptive testing, scored from 1–100, and have a median of 50. 18 Participants self-reported their bladder management, and when they used multiple management methods they were required to indicate which they considered primary.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, hospitalization will be prolonged ( Alattas et al, 2017 ). This not only increases the economic burden for patients and society but also lowers patient satisfaction ( Rabah et al, 2020 ; Small and Laycock, 2020 ; Dieu et al, 2021 ; Michael, 2021 ; Moghalu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors are to be commended for shedding light on what is consistently one of the greatest quality of life issues for the SCI population 2 and for highlighting that a shared decision-making model with a careful assessment of the patient's goals, home environment support, surgical risk, and functional capabilities is always paramount to optimizing outcome when selecting bladder management in our SCI patients.…”
Section: Editorial Commentmentioning
confidence: 99%